Frittzy Cafe / Muhammad Faiq Irfan Mohd Farid ... [et al.] - Mohd Farid, Muhammad Faiq Irfan; Johari, Adib Iskandar; Zulkifli, Muhammad Ikhwan; Hassan, Luqman Hakim; Juharuddin, Muhammad Naqib (2021)
Everyone in this world need food to live their lifes as its provides nutrients for our daily activity , growth and all function in our body . Its also make us grow active and healthy. But sometimes we need to get some taste of flavour some dishes because a famous American restaurateur said ,”food is not just eating energy. It is an experience.” Eating good food is one of the pleasure of life, so we tend to search for good and delicious food throughout our state , country and even go to travel around the world to find some good food to statisfy ourselves. When we travelling we will know the culture of certain places by eating their food. We willing to go far from home to search for delicious food, but do they know that they are tons of restaurants that serve mouth-watering food nearby them.